A corrugated pipe polyethylene composite and a method for producing the same
Patent Information
- Application Number
- CN202611244502.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种波纹管聚乙烯复合材料及其制备方法,解决了现有形状记忆波纹管依赖外部热源触发修复,在埋地、夹层等封闭空间中无法实施,且修复后无任何可追溯标记,不利于管道系统运行状态的长期跟踪和维护决策的问题
[0019]本发明提供了一种波纹管聚乙烯复合材料及其制备方法。具备以下有益效果:
Smart Images

Figure CN122917416A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of corrugated pipe manufacturing technology, specifically to a corrugated pipe polyethylene composite material and its preparation method. Background Technology
[0002] Corrugated pipes are tubular elastic elements with periodic transverse corrugations on their walls, widely used in pipeline connections, cable protection, vibration damping, and other engineering fields. They achieve sealing, displacement compensation, and vibration damping functions through the elastic deformation of the corrugated structure, and recover to their initial shape based on the material's own elasticity after the external load is removed. Polyethylene, due to its good flexibility, chemical corrosion resistance, and processing fluidity, has become one of the mainstream materials for corrugated pipe manufacturing.
[0003] Existing technologies already include solutions for incorporating shape memory functionality into polyethylene corrugated pipes. Patent CN109721794B discloses a polyethylene composite material for corrugated pipes, prepared by mixing and extruding 42-66 parts of polyethylene, 12-20 parts of polyphenylene sulfide (PPS), toughening agents, flame retardants, compatibilizers, and other components. This material utilizes the network dispersion structure formed by PPS within the polyethylene matrix, causing the polyethylene grains to exhibit rubber elasticity rather than a flowing state after melting. Corrugated pipes produced in this way can recover their shape after collapse and deformation by heating, with a recovery rate of no less than 90% and a recovery time of no more than 100 seconds. This effectively solves, to some extent, the problem of irreversible damage to corrugated pipes due to excessive loads.
[0004] In this solution, the shape restoration of the corrugated pipe relies entirely on an external heat source. However, corrugated pipes are often used in enclosed or inaccessible spaces such as underground pipe galleries, building mezzanines, and equipment interiors. Using external heating equipment like hot air guns or ovens in these environments presents practical difficulties, including limited operating space, significant heat loss, and uneven heating, often making it impossible to effectively heat deformed areas. This means that the material's shape memory properties are ineffective in situations lacking operable heating conditions. Furthermore, the repaired corrugated pipe shows no traceable changes in appearance, making it impossible for maintenance personnel to visually determine which pipe sections were deformed and repaired, hindering long-term monitoring of the pipeline system's operational status and subsequent maintenance decisions. Summary of the Invention
[0005] Technical problems to be solved
[0006] To address the shortcomings of existing technologies, this invention provides a corrugated polyethylene composite material and its preparation method, which solves the problems of existing shape memory corrugated pipes relying on external heat sources for repair, which cannot be implemented in enclosed spaces such as underground or interlayer structures, and the lack of any traceable markings after repair, which is not conducive to long-term tracking and maintenance decisions of pipeline system operation status.
[0007] Technical solution
[0008] To achieve the above objectives, the present invention provides the following technical solution: a corrugated polyethylene composite material, made from raw materials comprising the following components: 45-70 parts by weight of polyethylene 10-25 parts by weight of polyphenylene sulfide toughening agent 10-25 parts by weight 5-12 parts by weight of flame retardant 3-10 parts by weight of compatibilizer Antioxidant 0.1-1.5 parts by weight Lubricant 0.2-1.0 parts by weight 0.3-8 parts by weight of nano-conductive filler 0.5-5 parts by weight of thermochromic microcapsules; The nano-conductive filler forms a three-dimensional conductive network in the polyethylene composite matrix, and the color-changing initiation temperature of the thermochromic microcapsule is 90-130℃.
[0009] Preferably, the nano-conductive filler is at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, and graphene nanosheets, with an average length of 1-50 μm and an average diameter of 5-50 nm.
[0010] Preferably, the thermochromic microcapsule is composed of a wall material and a core material, wherein the core material contains an electron-donating dye and a color developer, and the wall material is one of melamine-formaldehyde resin, urea-formaldehyde resin, or polyurethane.
[0011] Preferably, the polyethylene is high-density polyethylene, and its melt flow rate is 0.3-3.0 g / 10 min at 190℃ / 2.16 kg; the polyphenylene sulfide has a weight-average molecular weight of 20,000-60,000.
[0012] Preferably, the toughening agent is an ethylene-octene copolymer or an ethylene-butene copolymer, and the compatibilizer is maleic anhydride-grafted polyethylene with a maleic anhydride grafting rate of 1.2-2.8%.
[0013] Preferably, the weight ratio of the nano-conductive filler to the thermochromic microcapsule is 1:0.5-1:2.
[0014] A method for preparing a corrugated polyethylene composite material includes the following steps: S1. Mix nano-conductive filler and polyethylene powder in a high-speed mixer at a weight ratio of 1:5-1:20 for 10-20 minutes, and then melt-extrude and granulate the mixture through a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 190-230℃. S2. Mix the thermochromic microcapsules and toughening agent at a weight ratio of 1:3-1:10 for 5-10 minutes, and then melt-extrude and granulate them through a twin-screw extruder to obtain the color-changing masterbatch. The extrusion temperature is 120-160℃. S3. Add the conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant to a high-speed mixer and mix for 8-15 minutes. After discharge, add the mixture to a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder are 215-235℃, 225-245℃, 250-265℃, 250-265℃, 255-270℃, 255-275℃, 260-275℃, 260-280℃, 265-280℃, and 265-290℃, respectively.
[0015] Preferably, the screw speed of the twin-screw extruder in S1 is 300-500 rpm, and the screw speed of the twin-screw extruder in S3 is 350-450 rpm.
[0016] A corrugated pipe is made of polyethylene composite material through melt extrusion, vacuum shaping, corrugation forming, and cooling cutting. The content of nano-conductive filler in the pipe wall of the corrugated pipe varies along the thickness direction of the pipe wall and does not exceed 30% of the average content.
[0017] Preferably, after the wall of the corrugated pipe is bent or compressed, the resistivity of the deformed area changes by 50%-2000% relative to that before deformation; after the deformed area is heated to 100-135°C and held for 20-90 seconds, the shape recovery rate is not less than 88%, and the deformed area exhibits a color different from that of the non-deformed area.
[0018] Beneficial effects
[0019] This invention provides a corrugated polyethylene composite material and its preparation method. It has the following beneficial effects: 1. This invention provides a corrugated pipe polyethylene composite material and its preparation method. The invention introduces nano-conductive fillers into the polyethylene matrix to form a three-dimensional conductive network. When a portion of the corrugated pipe deforms, the change in the conductive network structure in that area leads to an increase in local resistivity. Under energized conditions, the Joule heat power density in the deformed area increases accordingly, thus spontaneously heating to the shape memory trigger temperature. The entire repair process requires no external heat source and can be implemented with electricity, making it suitable for underground, interlayer, and enclosed spaces where hot air guns or ovens cannot be used. Simultaneously, the change in resistivity itself can serve as an electrical criterion for the degree of deformation, providing a signal basis for intelligent monitoring.
[0020] 2. This invention provides a corrugated polyethylene composite material and its preparation method. The invention introduces a thermochromic microcapsule component, with the color-changing initiation temperature set within the shape memory triggering temperature range. During the electrical repair process, the deformed area changes color as the temperature rises, and this color mark is retained after repair. Maintenance personnel can identify the location of deformation simply by visual inspection, without the need for detection equipment, thus overcoming the defect of existing shape memory corrugated pipes that leave no visible trace after repair. Attached Figure Description
[0021] Figure 1 The resistivity variation curves of the composite material under different amounts of nano-conductive fillers are shown. Figure 2 A comparison of the resistivity change rate after deformation under different amounts of nano-conductive filler added; Figure 3 The curves showing the relationship between shape recovery rate and recovery time under different energizing voltages; Figure 4 The bar charts show the comparison of shape recovery rate and recovery time between Examples 1-6 and Comparative Examples 1-2. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] The raw material information used in each embodiment is as follows: Polyethylene: High-density polyethylene, with a melt flow rate of 0.3-3.0 g / 10 min at 190℃ / 2.16 kg, using HDPE 7600M produced by Yanshan Petrochemical.
[0024] Polyphenylene sulfide: weight average molecular weight 20,000-60,000, density 1.34-1.38 g / cm³, using PPS A900 manufactured by Toray Industries, Japan.
[0025] Toughening agent: ethylene-octene copolymer, specifically POE8200 manufactured by Dow Chemical.
[0026] Compatibilizer: Maleic anhydride-grafted polyethylene, with a maleic anhydride grafting rate of 1.2-2.8%, using PE-g-MAH produced by Guangzhou Baichen.
[0027] Flame retardant: Low-halogen bromine flame retardant, phosphorus content ≥9.5wt%, bromine content ≤30wt%.
[0028] Antioxidant: Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Antioxidant 1010).
[0029] Lubricant: PE wax.
[0030] Nanoconductive filler: Multi-walled carbon nanotubes, with an average length of 1-50 μm, an average diameter of 5-50 nm, and a purity of ≥95%.
[0031] Thermochromic microcapsules: The wall material is melamine-formaldehyde resin, and the core material contains electronic dyes and color developers. The color change initiation temperature is 100-135℃. Example 1
[0032] Weigh the following raw materials by weight: 66 parts polyethylene, 12 parts polyphenylene sulfide, 12 parts toughening agent, 6 parts flame retardant, 4 parts compatibilizer, 0.3 parts antioxidant, 0.5 parts lubricant, 0.5 parts nano conductive filler, and 0.5 parts thermochromic microcapsules.
[0033] Nano-conductive fillers and polyethylene powder were mixed at a weight ratio of 1:5 in a high-speed mixer for 10 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 200℃. Thermochromic microcapsules and toughening agents were mixed at a weight ratio of 1:5 for 8 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain color-changing masterbatch at an extrusion temperature of 150℃.
[0034] The conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant were added to a high-speed mixer and mixed for 10 minutes. After discharge, the mixture was fed into a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder were 220℃, 230℃, 255℃, 255℃, 260℃, 260℃, 265℃, 265℃, 270℃, and 270℃, respectively, and the screw speed was 400 rpm.
[0035] When the amount of nano-conductive filler added is 0.5 parts, the content of carbon nanotubes in the composite material is approximately 0.4 wt%. The percolation threshold of the multi-walled carbon nanotube / high-density polyethylene composite system is typically between 1.0 wt% and 2.0 wt%. In this embodiment, the filler content is lower than the percolation threshold, resulting in a sparser conductive network. Therefore, the composite material has a higher initial resistivity and correspondingly higher sensitivity to deformation. The resistivity change rate after deformation can reach 1800%.
[0036] The composite material obtained above was melt-extruded, vacuum-formed, corrugated, and cooled and cut to obtain a corrugated pipe sample. The corrugated pipe sample was tested under bending deformation conditions. The resistivity of the deformed area changed by 1800% compared with that before deformation. After being heated to 120°C and held for 45 seconds, the shape recovery rate was 90.2%, and the deformed area showed a color different from that of the non-deformed area. Example 2
[0037] Weigh the following raw materials by weight: 57 parts polyethylene, 16 parts polyphenylene sulfide, 15 parts toughening agent, 7 parts flame retardant, 5 parts compatibilizer, 0.6 parts antioxidant, 0.3 parts lubricant, 2 parts nano-conductive filler, and 1.5 parts thermochromic microcapsules.
[0038] Nano-conductive fillers and polyethylene powder were mixed in a high-speed mixer at a weight ratio of 1:10 for 15 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 210℃. Thermochromic microcapsules and toughening agents were mixed at a weight ratio of 1:8 for 10 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain color-changing masterbatch at an extrusion temperature of 140℃.
[0039] The conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant were added to a high-speed mixer and mixed for 12 minutes. After discharge, the mixture was fed into a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder were 230℃, 240℃, 260℃, 260℃, 265℃, 270℃, 270℃, 275℃, 275℃, and 280℃, respectively, and the screw speed was 350 rpm.
[0040] The corrugated pipe sample was tested under compression deformation conditions. The resistivity of the deformed area changed by 650% compared with that before deformation. After being heated to 125°C and held for 60 seconds, the shape recovery rate was 93.8%. The deformed area showed a color that was different from that of the non-deformed area. Example 3
[0041] Weigh the following raw materials by weight: 50 parts polyethylene, 18 parts polyphenylene sulfide, 18 parts toughening agent, 8 parts flame retardant, 6 parts compatibilizer, 0.4 parts antioxidant, 0.5 parts lubricant, 4 parts nano conductive filler, and 3 parts thermochromic microcapsules.
[0042] Nano-conductive fillers and polyethylene powder were mixed at a weight ratio of 1:15 in a high-speed mixer for 20 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 220℃. Thermochromic microcapsules and toughening agents were mixed at a weight ratio of 1:10 for 10 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain color-changing masterbatch at an extrusion temperature of 160℃.
[0043] The conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant were added to a high-speed mixer and mixed for 15 minutes. After discharge, the mixture was fed into a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder were 225℃, 235℃, 260℃, 260℃, 265℃, 270℃, 270℃, 275℃, 275℃, and 285℃, respectively, and the screw speed was 450 rpm.
[0044] It should be noted that when the amount of nano-conductive filler added is 4 parts, the mass fraction of carbon nanotubes in the composite material is approximately 3.2 wt%, which significantly exceeds the percolation threshold, forming a complete three-dimensional conductive network in the composite material. At this point, the room temperature resistivity of the composite material drops to a low level, and the Joule heating effect is significant after energization. Testing a corrugated pipe sample under bending deformation conditions showed that the resistivity of the deformed region changed by 320% compared to before deformation. After heating to 130℃ and holding at that temperature for 75 seconds, the shape recovery rate was 95.6%, and the deformed region exhibited a color distinct from the non-deformed region. Example 4
[0045] Weigh the following raw materials by weight: 45 parts polyethylene, 20 parts polyphenylene sulfide, 20 parts toughening agent, 10 parts flame retardant, 8 parts compatibilizer, 0.2 parts antioxidant, 0.8 parts lubricant, 6 parts nano-conductive filler, and 4 parts thermochromic microcapsules.
[0046] Nano-conductive fillers and polyethylene powder were mixed at a weight ratio of 1:20 in a high-speed mixer for 20 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 230℃. Thermochromic microcapsules and toughening agents were mixed at a weight ratio of 1:3 for 5 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain color-changing masterbatch at an extrusion temperature of 120℃.
[0047] The conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant were added to a high-speed mixer and mixed for 8 minutes. After discharge, the mixture was fed into a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder were 235℃, 245℃, 265℃, 265℃, 270℃, 275℃, 275℃, 280℃, 280℃, and 290℃, respectively, and the screw speed was 350 rpm.
[0048] When the amount of nano-conductive filler increased to 6 parts, the conductive network became very dense, and the resistivity of the composite material was at a low level. The Joule heating effect was more pronounced under energized conditions, resulting in faster shape recovery. However, excessive filler content led to increased melt viscosity and decreased processing fluidity. Furthermore, excessive rigid filler constrained the movement of the polyethylene molecular chains, slightly reducing the shape recovery rate. In this embodiment, a corrugated pipe sample was tested under compression deformation conditions. The resistivity of the deformed region changed by 180% compared to before deformation. After heating to 135°C and holding for 90 seconds, the shape recovery rate was 92.1%, and the deformed region exhibited a color distinct from the non-deformed region. Example 5
[0049] Weigh the following raw materials by weight: 62 parts polyethylene, 14 parts polyphenylene sulfide, 14 parts toughening agent, 6 parts flame retardant, 4 parts compatibilizer, 0.5 parts antioxidant, 0.4 parts lubricant, 1 part nano-conductive filler, and 1 part thermochromic microcapsule.
[0050] Nano-conductive fillers and polyethylene powder were mixed at a weight ratio of 1:8 in a high-speed mixer for 12 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 205℃. Thermochromic microcapsules and toughening agents were mixed at a weight ratio of 1:6 for 8 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain color-changing masterbatch at an extrusion temperature of 145℃.
[0051] The conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant were added to a high-speed mixer and mixed for 10 minutes. After discharge, the mixture was fed into a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder were 225℃, 235℃, 260℃, 260℃, 265℃, 265℃, 270℃, 270℃, 275℃, and 275℃, respectively, and the screw speed was 400 rpm.
[0052] The corrugated pipe sample was tested under bending deformation conditions. The resistivity of the deformed area changed by 1200% compared with that before deformation. After being heated to 115℃ and held for 50s, the shape recovery rate was 91.5%. The deformed area showed a color that was different from that of the non-deformed area. Example 6
[0053] Weigh the following raw materials by weight: 48 parts polyethylene, 22 parts polyphenylene sulfide, 16 parts toughening agent, 9 parts flame retardant, 7 parts compatibilizer, 0.3 parts antioxidant, 0.6 parts lubricant, 8 parts nano-conductive filler, and 5 parts thermochromic microcapsules.
[0054] Nano-conductive fillers and polyethylene powder were mixed at a weight ratio of 1:12 in a high-speed mixer for 18 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 215℃. Thermochromic microcapsules and toughening agents were mixed at a weight ratio of 1:4 for 6 minutes, and then melt-extruded and granulated using a twin-screw extruder to obtain color-changing masterbatch at an extrusion temperature of 130℃.
[0055] The conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant were added to a high-speed mixer and mixed for 12 minutes. After discharge, the mixture was fed into a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder were 230℃, 240℃, 260℃, 260℃, 265℃, 270℃, 270℃, 275℃, 275℃, and 285℃, respectively, and the screw speed was 380 rpm.
[0056] The corrugated pipe sample was tested under compression deformation conditions. The resistivity of the deformed area changed by 120% compared with that before deformation. After being heated to 130℃ and held for 80s, the shape recovery rate was 89.8%. The deformed area showed a color that was different from that of the non-deformed area.
[0057] Comparative Example 1 Weigh the following raw materials by weight: 66 parts polyethylene, 12 parts polyphenylene sulfide, 12 parts toughening agent, 6 parts flame retardant, 4 parts compatibilizer, 0.3 parts antioxidant, 0.5 parts lubricant, and 0.5 parts nano-conductive filler. No thermochromic microcapsules are added.
[0058] The preparation method is the same as in Example 1.
[0059] A corrugated pipe sample was tested under bending deformation conditions. The resistivity of the deformed area changed by 1750% compared to before deformation. After being heated to 120℃ and held for 45 seconds, the shape recovery rate was 91.0%. After repair, the deformed area showed no color change and was indistinguishable from the non-deformed area.
[0060] Comparative Example 2 Weigh the following raw materials by weight: 57 parts polyethylene, 16 parts polyphenylene sulfide, 15 parts toughening agent, 7 parts flame retardant, 5 parts compatibilizer, 0.6 parts antioxidant, 0.3 parts lubricant, and 1.5 parts thermochromic microcapsules. No nano-conductive filler is added.
[0061] The preparation method is the same as in Example 2.
[0062] A corrugated pipe sample was tested under bending deformation conditions. Because the material is non-conductive, shape recovery could not be triggered by heating with electricity. After heating to 125°C using an external heat source (hot air gun) and holding at that temperature for 60 seconds, the shape recovery rate was 94.2%, and the deformed area exhibited a color distinct from the non-deformed area. The entire repair process relies on an external heat source and cannot be implemented in enclosed spaces such as underground or mezzanine structures.
[0063] Performance testing The composite materials obtained in Examples 1-6 and Comparative Examples 1-2 were tested for performance according to ISO standards. The test results are shown in Table 1.
[0064] Table 1 Performance test results of Examples 1-6 and Comparative Examples 1-2
[0065] Comparative Example 2 uses an external heat source for heating, and the recovery time is the external heating time.
[0066] From the data in Table 1 and Figure 1-4 It can be seen that all examples 1-6 achieved shape recovery triggered by power-on, with deformation recovery rates between 89.8% and 95.6% and recovery times between 45 and 90 seconds. When the amount of nano-conductive filler added increased from 0.5 parts to 8 parts, the resistivity change rate decreased from 1800% to 120%. The denser the conductive network, the smaller the relative impact of deformation on resistivity, but the corresponding increase in heating efficiency.
[0067] Comparative Example 1, without the addition of thermochromic microcapsules, exhibited shape recovery performance essentially equivalent to Example 1, but lacked color markings after repair. Comparative Example 2, without the addition of nano-conductive fillers, could not be repaired by electrical stimulation and required an external heat source. The mechanical properties of all examples (tensile strength 23.5-25.1 MPa, flexural modulus 790-858 MPa, notched impact strength 30.5-35.8 kJ / m²) remained at a good level, indicating that the introduction of nano-conductive fillers and thermochromic microcapsules did not significantly impair the basic mechanical properties of the composite material.
[0068] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A corrugated polyethylene composite material, characterized in that, Made from raw materials containing the following components: 45-70 parts by weight of polyethylene 10-25 parts by weight of polyphenylene sulfide toughening agent 10-25 parts by weight 5-12 parts by weight of flame retardant 3-10 parts by weight of compatibilizer Antioxidant 0.1-1.5 parts by weight Lubricant 0.2-1.0 parts by weight 0.3-8 parts by weight of nano-conductive filler 0.5-5 parts by weight of thermochromic microcapsules; The nano-conductive filler forms a three-dimensional conductive network in the polyethylene composite matrix, and the color-changing initiation temperature of the thermochromic microcapsule is 90-130℃.
2. The corrugated polyethylene composite material according to claim 1, characterized in that: The nano-conductive filler is at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, and graphene nanosheets, with an average length of 1-50 μm and an average diameter of 5-50 nm.
3. The corrugated polyethylene composite material according to claim 1, characterized in that: The thermochromic microcapsule is composed of a wall material and a core material. The core material contains an electronic dye and a color developer. The wall material is one of melamine-formaldehyde resin, urea-formaldehyde resin, or polyurethane.
4. The corrugated polyethylene composite material according to claim 1, characterized in that: The polyethylene is high-density polyethylene, and its melt flow rate is 0.3-3.0 g / 10 min at 190℃ / 2.16 kg; the polyphenylene sulfide has a weight-average molecular weight of 20,000-60,000.
5. The corrugated polyethylene composite material according to claim 1, characterized in that: The toughening agent is an ethylene-octene copolymer or an ethylene-butene copolymer, and the compatibilizer is maleic anhydride-grafted polyethylene with a maleic anhydride grafting rate of 1.2-2.8%.
6. The corrugated polyethylene composite material according to claim 1, characterized in that: The weight ratio of the nano-conductive filler to the thermochromic microcapsule is 1:0.5-1:
2.
7. A method for preparing a corrugated polyethylene composite material as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Mix nano-conductive filler and polyethylene powder in a high-speed mixer at a weight ratio of 1:5-1:20 for 10-20 minutes, and then melt-extrude and granulate the mixture through a twin-screw extruder to obtain conductive masterbatch at an extrusion temperature of 190-230℃. S2. Mix the thermochromic microcapsules and toughening agent at a weight ratio of 1:3-1:10 for 5-10 minutes, and then melt-extrude and granulate them through a twin-screw extruder to obtain the color-changing masterbatch. The extrusion temperature is 120-160℃. S3. Add the conductive masterbatch, color-changing masterbatch, and remaining polyethylene, polyphenylene sulfide, flame retardant, compatibilizer, antioxidant, and lubricant to a high-speed mixer and mix for 8-15 minutes. After discharge, add the mixture to a twin-screw extruder for melt blending, extrusion, and granulation. The temperatures of each section of the twin-screw extruder are 215-235℃, 225-245℃, 250-265℃, 250-265℃, 255-270℃, 255-275℃, 260-275℃, 260-280℃, 265-280℃, and 265-290℃, respectively.
8. The preparation method according to claim 7, characterized in that: The screw speed of the twin-screw extruder described in S1 is 300-500 rpm, and the screw speed of the twin-screw extruder described in S3 is 350-450 rpm.
9. A corrugated pipe, made from the polyethylene composite material according to any one of claims 1-6 by melt extrusion, vacuum shaping, corrugation forming, and cooling cutting, wherein the content of nano-conductive filler in the pipe wall of the corrugated pipe varies with the thickness of the pipe wall along a range not exceeding 30% of the average content.
10. The corrugated pipe according to claim 9, characterized in that: After the wall of the corrugated pipe is bent or compressed, the resistivity of the deformed area changes by 50%-2000% relative to that before deformation; after the deformed area is heated to 100-135℃ and held for 20-90s, the shape recovery rate is not less than 88%, and the deformed area exhibits a color different from the non-deformed area.
Citation Information
Patent Citations
A polyethylene composite material for corrugated pipes and its preparation method
CN109721794B